The shear instability energy: a new parameter for materials design?. (8th September 2017) - Kanani, M; Hartmaier, A; Janisch, R
Abstract: Reliable and predictive relationships between fundamental microstructural material properties and observable macroscopic mechanical behaviour are needed for the successful design of new materials. In this study we establish a link between physical properties that are defined on the atomic level and the deformation mechanisms of slip planes and interfaces that govern the mechanical behaviour of a metallic material. To accomplish this, the shear instability energy Γ is introduced, which can be determined via quantum mechanical ab initio calculations or other atomistic methods. The concept is based on a multilayer generalised stacking fault energy calculation and can be applied to distinguish the different shear deformation mechanisms occurring at TiAl interfaces during finite-temperature molecular dynamics simulations. We use the new parameter Γ to construct a deformation mechanism map for different interfaces occurring in this intermetallic. Furthermore, Γ can be used to convert the results of ab initio density functional theory calculations into those obtained with an embedded atom method type potential for TiAl. We propose to include this new physical parameter into material databases to apply it for the design of materials and microstructures, which so far mainly relies on single-crystal values for the unstable and stable stacking fault energy.